2006
DOI: 10.1242/jeb.02207
|View full text |Cite
|
Sign up to set email alerts
|

Color discrimination in the red range with only one long-wavelength sensitive opsin

Abstract: SUMMARY The basic precondition for color vision is the presence of at least two receptor types with different spectral sensitivities. The sensitivity of a receptor is mostly defined by the opsin-based visual pigment expressed in it. We show here, through behavioral experiments, that the nymphalid butterfly Heliconius erato, although it expresses short and medium wavelength opsins and only one long wavelength opsin, discriminates colors in the long-wavelength range (590 nm, 620 nm and 640 nm), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
149
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 110 publications
(159 citation statements)
references
References 57 publications
(75 reference statements)
9
149
1
Order By: Relevance
“…These data suggest that a sexually dimorphic eye may represent the ancestral state in insects. However, other more basal butterflies that have been examined, such as the swallowtail, the painted lady, the heliconian and the monarch butterfly, do not have sexually dimorphic patterns of opsin mRNA expression (Kitamoto et al, 1998;Briscoe et al, 2003;Sauman et al, 2005;Zaccardi et al, 2006). Rather, our data suggest that sexually dimorphic male eyes, expressing predominantly UV and B opsins, may have evolved independently in insects.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…These data suggest that a sexually dimorphic eye may represent the ancestral state in insects. However, other more basal butterflies that have been examined, such as the swallowtail, the painted lady, the heliconian and the monarch butterfly, do not have sexually dimorphic patterns of opsin mRNA expression (Kitamoto et al, 1998;Briscoe et al, 2003;Sauman et al, 2005;Zaccardi et al, 2006). Rather, our data suggest that sexually dimorphic male eyes, expressing predominantly UV and B opsins, may have evolved independently in insects.…”
Section: Discussionmentioning
confidence: 55%
“…It is therefore possible that L. rubidus has pentachromatic vision in ventral retina based primarily on four opsins and this pink non-opsin pigment. Filtering pigments of similar effect have been observed for the LW receptors of Papilio xuthus and Pieris rapae (Arikawa et al, 1999;Wakakuwa et al, 2004), and have been shown to be important for butterfly color vision (Zaccardi et al, 2006).…”
Section: Non-overlapping Expression Of Uvrh Brh1 and Brh2mentioning
confidence: 61%
See 3 more Smart Citations